Physical and biological events across the Frasnian-Famennian boundary (Late Devonian) in continuous oxic carbonate successions in the western Tethys (Carnic Alps of Italy and Austria) - Farabegoli, Enzo; Perri, Maria Cristina; Spalletta, Claudia; Joachimski, Michael; Andrew, Anita; Pondrelli, Monica (Bollettino Della Societa Paleontologica Italiana, 2023)
Two Upper Devonian stratigraphic sections Pramosio A (PRA) and Freikofel T (FRKT) in the Carnic Alps of Italy and adjacent southern Austria representing continuous, entirely calcareous oxic sedimentation spanning the Frasnian-Famennian (Fr-Fm) boundary, were analysed for conodont biostratigraphy, facies and geochemistry. Lithologies are mainly packstone and wackestone interbedded with rudstones. Microbial matter is associated with packstones and wackestones in the latest Frasnian continuing through to the base of the Famennian. Intervals of black limestone and anoxic black shale with bituminous layers are absent from both sections. Microfacies analysis, focused mainly on the Fr-Fm boundary interval, discriminated nine facies in the PRA section and six in the FRKT section, all representing water depths of a few dozens of metres. The former is interpreted as having been deposited along the middle or upper part of a slightly inclined carbonate ramp (<2°), the latter along or at the base of a metastable carbonate ramp (<6°). Pramosio A section ranges from Frasnian Zone 12 to the Pseudopolygnathus granulosus Zone, Freikofel T from Zone 13a to the Palmatolepis termini Zone. The conodont study focused on biodiversity variation during the late Frasnian biologic crisis and across the Fr-Fm transition up to the end of recovery in the Palmatolepis minuta minuta Zone. Polygnathids dominate until the upper part of Zone 13b when palmatolepids become prevalent. In Zone 13c, their dominance continued into the lower Famennian. Increase of icriodids was paralleled by the onset of palmatolepid dominance. The end-Frasnian biological crisis impacted heavily on conodonts, extinguishing the ancyrodellids and wiping out all palmatolepids except for a single species, Palmatolepis ultima. The scenario cannot be attributed to anoxia because the seawaters were well oxygenated. The Lower and Upper Kellwasser extinction events (LKWE and UKWE), connected with the end-Frasnian biologic crisis were identifiable by conodonts even in the absence of sedimentary signatures of anoxic facies. The Lower Kellwasser Event is associated with a decreasing-temperature trend. Two phases of the Upper Kellwasser Event have been discriminated. Both are connected with decreasing temperature based on conodont apatite δ18O. Enhanced burial of organic matter is indicated by increase in δ13C measured on whole-rock carbonate in the Pramosio A section from the uppermost Zone 13b to the base of the Famennian. This positive shift in δ13Ccarb pre-dates the shift in δ18O. Conodont abundances are higher in Pramosio A than in Freikofel T. Exceptional abundances occur in Zone 13b in PRA section, peaking in pelagic environments with palmatolepid conodonts concurrent with increase of other pelagic biota, especially ammonoids and radiolarians. This is consistent with transgressive phases. Low abundances often coincide with rudstone levels equating with low-stand phases. Those in the early Famennian are inferred to reflect events during the worldwide biological crisis. Three transgressive-regressive cycles have been identified during Zone 13b in the Carnic Alps; the regressive trend of the last cycle persisted throughout Zone 13c when the basin reached low-stand conditions followed by a transgressive phase immediately above the Fr-Fm boundary. The transgressive-regressive cycles were of high frequency and possibly of fourth order because the time interval between the lower and upper Kellwasser positive δ13C excursions, equivalent to the interval uppermost Zone 12 to uppermost Zone 13c, has been estimated at about 600 kyr.
CRIS-Team Scopus Importer:2023-10-06
Keywords: biostratigraphy; conodonts; Depositional environments; extinction; Lower Kellwasser Event; post-event recovery; stable isotopes; Upper Kellwasser Event